How important is the non-governmental sector for providing public health services in India?. Issue 5 (4th July 2022) - Das, Nimai
ABSTRACT: The non-governmental but not-for-profit sector seems to bridge the gap apparent in a shortage of government resources and unaffordable for-profit services in the healthcare market of India. Based on a background study about the non-governmental organisation for official health accounts, it was found to be imperative, especially in providing preventive and promotive healthcare services. To the current health expenditure of the country, this sector contributes around 2.1%, with funds generated largely as grants from governments and foreign sources. Indeed, financial contribution is not as imperative as the ability to reach grassroots for providing healthcare, which should be considered as an opportunity to augment the capacity of the health system, especially during the COVID-19 pandemic.